Immunopathogenesis of bovine neosporosis throughout gestation - Canton, German Jose (College of Medicine and Veterinary Medicine, University of Edinburgh, 2019)
Tesis para obtener el grado de Doctor of Philosophy, del College of Medicine and Veterinary de University of Edinburgh, 2013.